1986
DOI: 10.1111/j.1600-0897.1986.tb00061.x
|View full text |Cite
|
Sign up to set email alerts
|

Graft‐vs‐Host Reaction Induced by Para‐aortic Lymph Nodes During Estrous and Diestrous Stages

Abstract: Mouse uterine draining lymph node (UDLN) cells, or soluble factors released by them in both phases of the estrous cycle were examined in the graft‐vs‐host (GVH) assay. The immune response during the estrous phase was significantly decreased as compared with diestrous phase; 24‐hour culture supernatant of UDLN cells was also able to decrease GVH activity mounted in F1 hybrids. This difference in reactivity was not found when peripheral nodes (PN) or spleen cells were tested. These results show that in physiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Other studies have shown that sex hormones can also modulate lymphocyte function at sites different from the female genital tract. Diminished graft versus host capacity of donor uterine draining lymph node cells was observed at estrus (Bonaparte et al 1986) and was associated with a decrease in the percentage and absolute number of CD8 cells (Colombo et al 1988). Moreover, studies performed in humans using peripheral blood mononuclear cells indicated that the secretion of TNF-a and IL-4 was directly correlated with the levels of estrogens in pre menopausal women (Schwarz et al 2000, Verthelyi andKlinman 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that sex hormones can also modulate lymphocyte function at sites different from the female genital tract. Diminished graft versus host capacity of donor uterine draining lymph node cells was observed at estrus (Bonaparte et al 1986) and was associated with a decrease in the percentage and absolute number of CD8 cells (Colombo et al 1988). Moreover, studies performed in humans using peripheral blood mononuclear cells indicated that the secretion of TNF-a and IL-4 was directly correlated with the levels of estrogens in pre menopausal women (Schwarz et al 2000, Verthelyi andKlinman 2000).…”
Section: Discussionmentioning
confidence: 99%